2021
DOI: 10.1155/2021/9981738
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Antibiotics from Real Hospital Wastewater by Cold Plasma Technique

Abstract: Hospital wastewater contains a complex mixture of bioactive substances and microorganisms that are deleterious to humans and aquatic animals. In this study, four antibiotics, namely, ofloxacin, ciprofloxacin, cefuroxime, and amoxicillin, respectively, from the wastewater of seven hospitals in Ho Chi Minh City, Vietnam, were monitored. The results revealed that the wastewater from these hospitals is contaminated with at least one of the antibiotics. In addition, the degradation capacity of the antibiotics by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…For instance, NO, NO 2 , NO 3 ˙, NO 3 − and ONOO − showed immunogenic cell death in cancer cells and were also beneficial in increasing crops on the field [ 63 , 64 ]. On the other hand, OH˙, O 3 and H 2 O 2 species play an essential role in bacterial decontamination and wound healing purposes [ 65 , 66 , 67 ]. Hence, our investigation results assist in developing an efficient approach to the selective production of ROS and RNS.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, NO, NO 2 , NO 3 ˙, NO 3 − and ONOO − showed immunogenic cell death in cancer cells and were also beneficial in increasing crops on the field [ 63 , 64 ]. On the other hand, OH˙, O 3 and H 2 O 2 species play an essential role in bacterial decontamination and wound healing purposes [ 65 , 66 , 67 ]. Hence, our investigation results assist in developing an efficient approach to the selective production of ROS and RNS.…”
Section: Resultsmentioning
confidence: 99%
“…Such complex outcomes of the CAPP-based treatment would be highly beneficial for decontamination of wastewaters from hospitals and clinics. For instance, Nguyen et al 37 monitored the degradation efficacy of ofloxacin, ciprofloxacin, cefuroxime and amoxicillin of the CAPP-based wastewater treatment plant in one of the Vietnam hospitals. The achieved drug degradation rates were high, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…exceeding 99% for cefuroxime and ciprofloxacin and 72% for amoxicillin and ofloxacin, though, sadly, the authors did not study the variation in the amount of the detected coliforms prior and post the CAPP-treatment. This aspect would be interesting to address in the future especially in a view of high microbiological contamination rates of wastewaters of a hospital origin (1.5 × 10 5 − 1.4 × 10 7 CFU/100 mL; Nguyen et al 37 ). A possible drawback of a CAPP-involving approach was listed by Gilmore et al 38 , who reported induction of a transient, dormant, metabolically inactive phenotype providing elevated tolerance to stress in the CAPP-exposed microbial population, leading to generation of persister or viable but non-cultivable (VBNC) cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, our findings of selected parameters of treated hospital wastewater were in acceptable limits, but still, it may cause genotoxicity indicating that there were some other factors responsible in treated hospital wastewater, which probably may not have been efficiently removed during the treatment process and have therefore, caused cytotoxicity. Also, several studies have reported that antibiotics and their residues can assist the generation of antibiotic‐resistant bacteria and genes even at low concentration, which could be a major hazard to human health globally (Ben et al, 2019; Fair & Tor, 2014; Nguyen et al, 2021). Micronuclei may originate either from acentric fragments of a chromosome or from the whole chromosomes which are unable to migrate with the rest of the chromosomes during the anaphase of cell division.…”
Section: Discussionmentioning
confidence: 99%